Synthesis, characterization and application of visible-light-responsive CuSO4-doped TiO2 photocatalyst for methylene blue degradation - Mercado, Chinee H.; De Luna, Mark Daniel G. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Synthetic dyes are the main environmental contaminants in textile industry e. In this study, visible-light photocatalytic degradation of methylene blue (MB) was carried out using CuSO4-doped TiO2 photocatalysts prepared via a sol-gel process. The effects of photocatalyst synthesis parameters (dopant concentration, HNO3-to-Ti(OBu)4 ratio, and calcination time) on catalyst properties and MB degradation were investigated. CuSO4- TIO2 photocatalyst with dopant concentration, HNO3-to-Ti(OBu)4 ratio, and calcination temperature of 0.21 mol%, 0.10 (v/v), and 300°C, respectively, achieved 97% MB degradation with an apparent rate constant (kapp = 29.12 x 10-3 min-1) that is higher compared to commercial Degussa P25 (kapp = 0.01 x 10-3 min-1). Characterization studies including UV-vis diffusive reflectance spectroscopy (UV-vis-DRS), scanning electron microscopy (SEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS), confirmed that CuSO4-TiO2 is active under visible light, consisted of spherical nanoparticles, is in anatase phase with an average crystallite size of 5.04 nm, and is composed of titanium, oxygen, carbon, nitrogen and copper atoms, respectively. The effects of photocatalyst dosage, initial dye concentration, pH, light intensity, light wavelength, and salinity on MB degradation was also investigated in this study.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Sewage -- Purification -- Color removal; Water -- Purification -- Photocatalysis